Discovery of the aleocharine tribe Diestotini in Japan, Ogasawara Islands, with description of a new species of the genus Diestota Mulsant & Rey (Coleoptera: Staphylinidae) - Hashizume, Takuto; Kishimoto, Toshio (Zootaxa, 2025)
Diestota (Diestota) ogasawarana Hashizume & Kishimoto, sp. nov. (Coleoptera: Staphylinidae: Aleocharinae: Diestotini) is described as the first representative of the genus Diestota Mulsant & Rey, 1870, and the tribe Diestotini from Japan. Aphaenoglossa Peyerimhoff, 1937, the subgenus of Diestota, is elevated to the generic rank.